# algebra

posted by .

On the problem 9x+7y=4
x=23-4y
solve by substitution

Do you mean to put 9 in the place of x=23-4y (9x=23-4y)

• algebra -

It would look like this...9(23-4y)+7y=4
Then you simplify
9*23=207
9*-4y=-36y
so you now have
207-36y+4y
Combine like terms
-36y+4y=-32
-32y=4
Finally you divide
the end reslut is y=-8

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### algebra

solve by substitution 5x-2y = -5 y - 5x = 3 could someone take a min a show me how to do this problem by steps so i can do the rest of my problems and wait a min so i may ask questions. I m failing my algebra class and desparately …
2. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
3. ### Algebra1!Plz help I have test 2morrow!!!

so would the new eqaution be... 2x+8=10 then.. 2x=2 x=1?
4. ### Algebra

Can someone show me step by step how to do this problem to have an example to go by so I will be able to do my other problems. Thanks Solve by substitution 4x-12y=5 -x+3y=-1 I know that you have solve one of the equations. I have picked …
5. ### Algebra Question

I did a problem and used the substitution method and it took me forever to solve by hand. Is there a shorter way to show how this problem was done. The problem was x+y+z=7,x-y+2z=7,2x+y+3z=15 The final answer came out to be x=4 z=2 …
6. ### algebra

i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of equations …
7. ### Algebra

The problem is 9x+4y=-12 x=26-5y Solve by substitution method
8. ### algebra

Here is my question. How do you solve th substitution method in this problem?
9. ### Math

Ok so you're supposed to solve the system by method of substitution. And the problem is: -2/3x + y = 2 2x - 3y = 6 So i put y= 2/3x into the second equation which looks like: 2x - 3(2/3x + 2) = 6 and then 2x-2x-6=6 So like everything …
10. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …

More Similar Questions

Post a New Question